Evolution and Development of Customary Law in the Archipelago: From Tradition to Modernity - Anis Noviya (PT. Anagata Sembagi Education, 2024)
Customary law in the archipelago is a deep cultural heritage and plays a significant role in the lives of traditional communities. This article examines the evolution and development of customary law in Indonesia, from its traditional roots to its adaptation in a modern context. This study aims to understand how customary law, which was originally local and traditional, has adapted to social, political, and legal changes that have occurred at the national and global levels. Through a historical approach and literature analysis, this article identifies important stages in the evolution of customary law, including the influence of colonialism, integration with the national legal system, and post-independence legal reform. The main focus lies on how customary law adapts to the dynamics of modernity while maintaining its cultural essence. This study also explores the challenges faced by customary law in facing globalization and social change, as well as efforts to maintain its sustainability amidst an increasingly dominant national legal system. The results show that customary law has undergone significant changes but continues to play an important role in society. Adaptation of customary law includes adjusting norms and practices to align with national law and modern values, without losing its original cultural identity. This article concludes that although customary law faces various challenges, it continues to contribute to the preservation of culture and dispute resolution in indigenous communities, as well as playing a role in the development of more inclusive national laws.